“Crimean Issue” and the Civilizational Foundations of Russia’s Foreign Policy in the Context of a Global Hybrid War - Z. R. Gapizov; N. I. Kharitonova (Евразийская интеграция: экономика, право, политика)
The  article examines the role of the phenomenon of civilizational identity in Russia’s foreign policy in the context of the current hybrid confrontation based on the study of the parameters of the possibilities for resolving the “Crimean issue”. The essence of the global hybrid conflict between Russia and the West is analyzed, the possibilities of using the concept of civilizational identity as a   geopolitical toolkit  are determined. Aim . Unleashing the potential of the concept of civilizational identity in the global hybrid confrontation with the collective West in the context of the formation of a  polycentric  world order based on the experience of resolving the “Crimean issue”.Tasks. Determine the essence and parameters of the global geopolitical conflict in modern world political conditions; to characterize the role of the civilizational identity of the Crimean population in solving the “Crimean issue”, to identify the potential of civilizational identity for solving domestic and foreign political problems, taking into account Russian national interests.Methods. Geopolitical approach, system analysis, retrospective method, document analysis.Results . The study showed the need for the formation and conceptualization of the civilizational foundations of Russia’s foreign policy. This should be a   larger-scale policy  that is creative in nature and translates the principles of justice and peaceful interstate relations. Changes in Russian foreign policy thinking can bring positive results  — to strengthen the Russian statehood, Russia’s international subjectivity, lay the foundations for a  truly polycentric  world order and expand the boundaries of the Russian world.Conclusions . The concept of civilizational identity acts as a   universal an d effective tool for solving the “Crimean issue” and therefore should be considered both as a  basic social  value, and as a  mandatory category of state document strategies, and as a  formative element in th e information sphere.